Valkyrie - Singer, Bryan; Cruise, Tom, 1962-; Wilkinson, Tom, 1948-; Stamp, Terence; MGM Home Entertainment Inc. ([United States] : Metro Goldwyn Mayer Home Entertainment, 2009)
Based on the incredible true story of Colonel Claus von Stauffenberg and his ingenious assassination plot targeting Adolf Hitler, this engrossing thriller reenacts the daring operation to eliminate one of the most evil tyrants the world has ever known.
Title from web page.
Originally released as a motion picture in 2008.
Tom Cruise, Tom Wilkinson, Terence Stamp.
MPAA rating: PG-13.
DVD; 5.1 Dolby Surround.
English, French or Spanish dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Schenk von Stauffenberg, Klaus Philipp, -- Graf, -- 1907-1944 -- Drama; Operation Valkyrie, 1944 -- Drama; Fiction films; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired